2009
DOI: 10.4172/jpb.1000099
|View full text |Cite
|
Sign up to set email alerts
|

Proteome of Salmonella Enterica Serotype Typhimurium Grown in a Low Mg2+/pH Medium

Abstract: To determine the impact of a low Mg2+/pH defined growth medium (MgM) on the proteome of Salmonella enterica serotype Typhimurium, we cultured S. Typhimurium cells in the medium under two different conditions termed MgM Shock and MgM Dilution and then comparatively analyzed the bacterial cells harvested from these conditions by a global proteomic approach. Proteomic results showed that MgM Shock and MgM Dilution differentially affected the S. Typhimurium proteome. MgM Shock induced a group of proteins whose ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…Recent studies highlighted the impact of de novo biotin biosynthesis especially for intracellular pathogens like M. tuberculosis, F. tularensis and S. Typhimurium (Dey et al, 2010;Napier et al, 2012;Shi et al, 2009;Woong Park et al, 2011). Here the in vivo attenuation of both the biotin auxotrophic DbioB mutant and the DbisC mutant emphasized the importance of biotin homeostasis during infection and demonstrated that BisC was crucial for full virulence of S. Typhimurium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies highlighted the impact of de novo biotin biosynthesis especially for intracellular pathogens like M. tuberculosis, F. tularensis and S. Typhimurium (Dey et al, 2010;Napier et al, 2012;Shi et al, 2009;Woong Park et al, 2011). Here the in vivo attenuation of both the biotin auxotrophic DbioB mutant and the DbisC mutant emphasized the importance of biotin homeostasis during infection and demonstrated that BisC was crucial for full virulence of S. Typhimurium.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, BisC allowed S. Typhimurium to regenerate biotin and methionine from their oxidized forms. This could be advantageous, especially for an intracellular lifestyle when energy sources and nutrients are scarce (Buchmeier & Libby, 1997;Chakravortty et al, 2002;Fields et al, 1986;Gallois et al, 2001;García-del Portillo et al, 2008;Hoiseth & Stocker, 1981;Shi et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such measurements, however, have been technically challenging due to the presence of vast amounts of host proteins (7). As a matter of fact, until now Ͼ90% of Salmonella proteomics research has focused on bacteria grown in vitro either from different strains or under culture conditions with various perturbations (8,9,10,11,12,13,14,15,16,17).…”
mentioning
confidence: 99%